Media Sosial dan Gaya Komunikasi - PRIMA AYU RIZQI MAHANANI (Komunikator, 2014)
The emergence of social media as a means to communicate has given the influence on the people’s life either directly or undirectly. It is because social media gives an opportunity to the users to interact and express their aspirations and inspirations. This media can even affect the communication styles of its users. This study aims to determine the impact of the use of social media which is based on web 2.0 on everyday communication styles of STAIN Kediri students. It also determines which variables that give dominant impact on communication styles. Based on the research, it can be concluded that there is a significant impact of the use of social media towards daily communication styles of STAIN Kediri students. The most significant variable which has great impact is the interaction in utilizing social media. It is because the student interaction with social media explains the relationship and deep involvement between the users and the social media that they use. Keywords: Social Media, Web 2.0, Communication Styles